2019
DOI: 10.1111/acel.13075
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive transient receptor potential canonical 7 (TRPC7) mediates aging‐associated tumorigenesis induced by ultraviolet B

Abstract: Aging, cancer, and longevity have been linked to intracellular Ca2+ signaling and nociceptive transient receptor potential (TRP) channels. We found that TRP canonical 7 (TRPC7) is a nociceptive mechanoreceptor and that TRPC7 channels specifically mediate the initiation of ultraviolet B (UVB)‐induced skin aging and tumor development due to p53 gene family mutations. Within 30 min after UVB irradiation, TRPC7 mediated UVB‐induced Ca2+ influx and the subsequent production of reactive oxygen species in skin cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…53 TRPC7 is showed to involved in initiation of UVB-induced aging and TRPC7 knocked down can suppress the UVB-induced aging processes. 54 Mouse vascular endothelial cells lacking TRPC5 display reduced β-galactosidase staining, implicating in the involvement of TRPC5 in development of senescence. 55…”
Section: Discussionmentioning
confidence: 99%
“…53 TRPC7 is showed to involved in initiation of UVB-induced aging and TRPC7 knocked down can suppress the UVB-induced aging processes. 54 Mouse vascular endothelial cells lacking TRPC5 display reduced β-galactosidase staining, implicating in the involvement of TRPC5 in development of senescence. 55…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a novel TRPV1-inhibiting peptide was demonstrated to attenuate UV-induced erythema and the expression of MMP-1, MMP-2, IL-6, and IL-8 in human skin in vivo ( Kang et al, 2017 ). Recently, a study found TRPC7 mediated UVB-induced Ca 2+ influx, UVB-induced ROS production, and UVB-induced epidermal aging in mice ( Hsu et al, 2020 ). These findings suggest that inhibition of specific TRP channels may delay skin aging.…”
Section: Dermatological Diseasesmentioning
confidence: 99%
“…Although numbers of TRP channels are identified by their characteristics and functions, several TRP channels are characterized by nociceptive TRP channels, including TRPA1, TRPC1/C3/C5/C6/C7, TRPM2/M3/M8 and TRPV1/V2/V3/V4, which are involved in the nociceptive pathway [19]. Interestingly, these nociceptive TRP channels in non-excitable or excitable cells potentially initiate the aging process due to excess Ca 2+ signaling from active nociceptive TRP channels upon continual environmental stimuli [11][12][13][14][15]. Environmental stimuli, such as bacterial endotoxins, oncovirus, di-(2-ethylhexyl)-phthalate (DEHP), particulate matters (PMs) or ultraviolet radiation have responding nociceptive TRP channels.…”
Section: Ca 2+ Signaling From Nociceptive Trp Channels Potentiates Initiation Of Cancer Progressionmentioning
confidence: 99%
“…The therapeutic targeting of Ca 2+ signaling provides a novel approach for treating cancer. Recently, nociceptive transient receptor potential (TRP) channels, which belong to a special group of TRP channels, have been involved in the nociceptive pathway and include members of the TRP ankyrin (TRPA), and TRP canonical (TRPC), TRP mucolipin (TRPM) and TRP vanilloid (TRPV) subfamilies that potentiate regulation of the aging process and tumorigenesis by Ca 2+ signaling [11][12][13][14][15]. This is different from the classical function of nociceptive TRP channels in excitable cells (neurons, muscle cells and some endocrine cells) that causes an influx of ions through the cell membrane to induce a depolarization of the cell which in turn triggers action potentials [16].…”
Section: Introductionmentioning
confidence: 99%